Identification of potential Campylobacter jejuni genes involved in biofilm formation by EZ-Tn5 Transposome mutagenesis - Teh, A.; Lee, S.; Dykes, Gary (BioMed Central, 2017)
Background: Biofilm formation has been suggested to play a role in the survival of Campylobacter jejuni in the environment and contribute to the high incidence of human campylobacteriosis. Molecular studies of biofilm formation by Campylobacter are sparse. Results: We attempted to identify genes that may be involved in biofilm formation in seven C. jejuni strains through construction of mutants using the EZ-Tn5 Transposome system. Only 14 mutants with reduced biofilm formation were obtained, all from one strain of C. jejuni. Three different genes of interest, namely CmeB (synthesis of multidrug efflux system transporter proteins), NusG (transcription termination and anti-termination protein) and a putative transmembrane protein (involved in membrane protein function) were identified. The efficiency of the EZ::TN5 transposon mutagenesis approach was strain dependent and was unable to generate any mutants from most of the strains used. Conclusions: A diverse range of genes may be involved in biofilm formation by C. jejuni. The application of the EZ::TN5 system for construction of mutants in different Campylobacter strains is limited.